The Influence of Multimedia Assisted Inquiry Learning Methods on My Heroes' Theme of Critical Thinking Skills and Learning Outcomes of Class IV Students of Elementary School - Purwanita, Yulis; Riyanto, Yatim; Suyanto, Totok (International Journal for Educational and Vocational Studies, 2019)
Researchers were interested in applying Inkuiry's learning method to teach my hero material. The media is called "Multimedia in the form of VCD". This study aims to analyze and observe the effect of inquiry learning methods on critical thinking skills and learning outcomes in grade IV elementary schools. This research was conducted at Elementary School 2 Experiment Malang, in the first semester of 2017-2018 school year. This study uses two classes namely the experimental class and the control class. The research sample was class IV B students as the experimental class and IVC class as the control class. The research instruments used were observation sheets of critical thinking skills and learning outcomes tests. Data analysis techniques used include normality test, homogeneous test, and independent test t-test. The results showed: Multiedia-assisted Inquiry learning method had an effect on critical thinking skills and learning outcomes of fourth grade students of SD Negeri Percobaan 2 Malang. Thus, the media is used as an alternative medium in social studies learning in the fourth grade.